Membimbing dengan Kearifan Lokal: Perawatan Spiritual dan Kehidupan Lansia di Desa Baru, Batang Kuis, Deli Serdang - Nabila Harahap; Kamalia (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
This study examines the implementation of spiritually oriented guidance grounded in local wisdom for the elderly in Desa Baru, Batang Kuis District, focusing on its modes of practice, its impact on religious consciousness and moral formation (akhlakul karimah), and the challenges and opportunities inherent in its application. Employing a descriptive qualitative approach, data were collected through participant observation, in-depth interviews, and documentation involving religious leaders, elderly participants, and their families. The findings reveal that spiritual guidance extends beyond conventional Qur'anic study circles and is embodied in enduring Mandailing religious traditions such as baiat, tawajjuh, suluk, Qur'anic recitation gatherings, and reflective sermons that function as a contextualized and elder-friendly form of Islamic da'wah. These practices foster a profound transformation of religiosity: from mechanical and normative routines to reflective-transcendental experiences that cultivate inner peace, strengthen faith, nurture virtuous character, and reinforce social solidarity. While challenges arise from physical limitations and the pressures of modernization, these are mitigated by strong familial, communal, and institutional support from mosques and nearby pesantren. Theoretically, this research advances the discourse on religious psychology and cultural da'wah by proposing a conceptual model of spiritual care for the elderly rooted in local wisdom that integrates cognitive, affective, social, and spiritual dimensions. Practically, it offers an inclusive, contextual, and sustainable framework for elder-oriented religious education, one that is adaptable for replication across diverse Muslim communities.